Levels of selected carcinogens and toxicants in vapour from electronic cigarettes. Issue 2 (6th March 2013) - Goniewicz, Maciej Lukasz; Knysak, Jakub; Gawron, Michal; Kosmider, Leon; Sobczak, Andrzej; Kurek, Jolanta; Prokopowicz, Adam; Jablonska-Czapla, Magdalena; Rosik-Dulewska, Czeslawa; Havel, Christopher; Jacob, Peyton; Benowitz, Neal
Abstract : Significance: Electronic cigarettes, also known as e-cigarettes, are devices designed to imitate regular cigarettes and deliver nicotine via inhalation without combusting tobacco. They are purported to deliver nicotine without other toxicants and to be a safer alternative to regular cigarettes. However, little toxicity testing has been performed to evaluate the chemical nature of vapour generated from e–cigarettes. The aim of this study was to screen e-cigarette vapours for content of four groups of potentially toxic and carcinogenic compounds: carbonyls, volatile organic compounds, nitrosamines and heavy metals. Materials and methods: Vapours were generated from 12 brands of e-cigarettes and the reference product, the medicinal nicotine inhaler, in controlled conditions using a modified smoking machine. The selected toxic compounds were extracted from vapours into a solid or liquid phase and analysed with chromatographic and spectroscopy methods. Results: We found that the e-cigarette vapours contained some toxic substances. The levels of the toxicants were 9–450 times lower than in cigarette smoke and were, in many cases, comparable with trace amounts found in the reference product. Conclusions: Our findings are consistent with the idea that substituting tobacco cigarettes with e-cigarettes may substantially reduce exposure to selected tobacco-specific toxicants. E-cigarettes as a harm reduction strategy among smokers unwilling to quit, warrants further study. (To view this abstract in Polish and German, please see the supplementary files online.)